Website usability and content accessibility of the top USA universities - Zaphiris, Panayiotis; Ellis, R. Darin (My University, 2001)
This study investigates whether the websites of the top USA universities are ranked high in terms of accessibility and usability and if these two measures are correlated. The usability and accessibility of the top fifty USA universities (USNews, 2001) were measured using two automatic evaluation tools: Bobby and LIFT. The results show a low compliance (30%) with Web site Content Accessibility Guide and a low usability rating for most of the university websites. The accessibility approval was found to correlate significantly with overall usability ratings of the websites. The size (in Kb) of the website was found to be a driving variable both for usability and accessibility.